2013
DOI: 10.1186/1471-2334-13-493
|View full text |Cite
|
Sign up to set email alerts
|

Identification of non-tuberculous mycobacteria isolated from clinical specimens at a tertiary care hospital: a cross-sectional study

Abstract: BackgroundNon-tuberculous mycobacteria (NTM) are opportunistic pathogens in immuno-compromised patients. They are also increasingly recognized as pathogens in immuno-competent individuals. Globally, an increase in NTM isolation is being reported with a varied geographic prevalence of different species around the world. There is lack of data on species distribution of these organisms from Pakistan. Treatment options differ according to the species isolated and its susceptibility profile. Knowledge of local spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…In relation to MAC, the 86% susceptibility rate to clarithromycin among the tested isolates in this current study from Lebanon was close to that reported from different parts of the world: USA (99%) [29], England (80%) [27] , Sweden (97%) [30], China (91%) [31], Japan (75%) [32], Taiwan (93%) [33], as well as Pakistan [34] and India (100%, each) [35]. Variation, however, was observed among the susceptibility rates of moxifloxacin and linezolid.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In relation to MAC, the 86% susceptibility rate to clarithromycin among the tested isolates in this current study from Lebanon was close to that reported from different parts of the world: USA (99%) [29], England (80%) [27] , Sweden (97%) [30], China (91%) [31], Japan (75%) [32], Taiwan (93%) [33], as well as Pakistan [34] and India (100%, each) [35]. Variation, however, was observed among the susceptibility rates of moxifloxacin and linezolid.…”
Section: Discussionsupporting
confidence: 83%
“…However, relatively susceptible isolates were reported from Greece (36%) [36], USA (<50%) [37], Netherlands (78%) [28] and China (86%) [31]. Such a wide range of variation in susceptibility was also noted for linezolid: current study from Lebanon (0%), Greece (4%) [36] Taiwan (13%) [33], Sweden (16%) [30], USA (<50%) [37], Pakistan (67%) [34] and China (93%) [31].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…An earlier study evaluating the distribution of NTM species across Pakistan suggested geographical variation across different regions, every area having its own distribution spectrum (Ahmed et al, 2013). The differences were especially discernible between urban centres where access to bronchoscopy and more in-depth diagnostic efforts contribute to the detection of a larger number of NTM cases.…”
Section: Mycobacterium Simiaementioning
confidence: 99%